Towards Organizational Citizenship Behavior and Religious Performance - Ramadania, Ramadania; Rosnani, Titik; Ratnasari, Sri Langgeng; Fauzan, Rizky; Apriandika, Muhammad Nahruddin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
The tendency of Islam is very thick in the Integrated Islamic Kindergarten (TKIT) and Integrated Islamic Elementary School (SDIT) circles. However, several schools focusing on increasing religious performance and management still need to fully interpret the role of organizational citizenship behaviour (OCB). The study concentrates on the role of OCB as a mediator in influencing spiritual motivation and spiritual leadership on religious performance in one of the kindergarten and primary schools from West Kalimantan. Quantitative methods, where in-depth exploration through surveys applies, support us, teachers and teaching staff. Resource persons were determined by a disproportionate stratified random sampling technique totalling 409 participants. We chose path analysis to interpret the data, so there are five essential points. The findings in the first model show that spiritual motivation and leadership have a significant effect on OCB. In the second model, spiritual motivation and OCB also significantly affect religious performance, whereas spiritual leadership does not. The implications of the output analysis indicate that the more spiritual motivation and spiritual leadership increase, the more it encourages OCB. Too, the more spiritual motivation and OCB increase, it also stimulates religious performance in the long term.